2021
DOI: 10.1177/1750458920971108
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an adjunctive analgaesic in the perioperative setting: A review of the literature

Abstract: Though arguably past the initial phase of the opioid epidemic, opioid-sparing or opioid-eliminating pain management regimens remain beneficial for patients and practitioners alike. Providing adequate analgaesia without relying on opioids is especially advantageous in the operative setting, as patients may be able to recover without deep levels of sedation or the need for a high amount of opioid medications. Despite being used primarily as a sedative over the past 20 years, dexmedetomidine, a centrally acting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Following surgery, the patient is transferred to the intensive care unit, where intravenous dexmedetomidine (0.1 μg/kg/h) is administered for sedation and analgesia [21]. Patients then self-administer intravenous oxycodone via a patient-controlled analgesia (PCA) device until analgesia is changed (on day 1-7 when PCA requirements become reduced) from intravenous opioid to the preferred agents sublingual buprenorphine or oral tapentadol (immediate-release and modified-release preparations) [22,23].…”
Section: Following Discharge From Hospital: Analgesia Managementmentioning
confidence: 99%
“…Following surgery, the patient is transferred to the intensive care unit, where intravenous dexmedetomidine (0.1 μg/kg/h) is administered for sedation and analgesia [21]. Patients then self-administer intravenous oxycodone via a patient-controlled analgesia (PCA) device until analgesia is changed (on day 1-7 when PCA requirements become reduced) from intravenous opioid to the preferred agents sublingual buprenorphine or oral tapentadol (immediate-release and modified-release preparations) [22,23].…”
Section: Following Discharge From Hospital: Analgesia Managementmentioning
confidence: 99%
“…High concentration of sevoflurane may increase the risk of cardiovascular depression, inhaled anaesthetic toxicity 8 and glycine absorption 9 . Dexmedetomidine is a highly selective alpha 2 ‐adrenergic receptor, known to produce sedation and analgesia without causing significant respiratory depression 10,11 . Many studies have shown that dexmedetomidine can reduce the effective concentration of inhalational anaesthetics 12,13 .…”
Section: Introductionmentioning
confidence: 99%